Penggunaan Corporate Social Responsibility Sebagai Intervening: Antara Komisaris Independen, Dewan Direksi, Komite Audit dan Kualitas Audit Terhadap Tax Avoidance - Agnestya Leonicha Yustin; Bahtiar Effendi (STATERA: Jurnal Akuntansi dan Keuangan, 2021)
The purpose of this study is to determine the effect of corporate governance (independent commissioners, board of directors, audit committee and audit quality) on tax avoidance with mediating role of corporate social responsibility. The type of research used in this study is quantitative method. The population in this study are all manufacturer companies listed on Indonesia Stock Exchange in 2016-2019 as many as 182 companies with annual reports for 4 years, namely from 2016-2019. Sample selection with purposive sampling method and counted by slovin formula. The analytical method used to test hypotheses is the multiple regression test. The results show that independent commissioners have no effect on tax avoidance in manufacturing companies listed on the IDX in 2016-2019, the board of directors has no effect on tax avoidance in manufacturing companies listed on the IDX in 2016-2019, audit committees have no effect on tax avoidance in companies manufacturers listed on the IDX in 2016-2019, audit quality has an effect on tax avoidance in manufacturing companies listed on the IDX in 2016-2019, CSR affects tax avoidance in manufacturing companies listed on the IDX in 2016-2019 and CSR can mediate the influence of corporate Governance on Tax Avoidance.